2017
DOI: 10.1161/strokeaha.117.018148
|View full text |Cite
|
Sign up to set email alerts
|

Serum Potassium Is Positively Associated With Stroke and Mortality in the Large, Population-Based Malmö Preventive Project Cohort

Abstract: Serum potassium, measured in early mid-life, was linearly associated with both incidence of ischemic stroke and intracerebral hemorrhage and all-cause mortality. An interaction with serum sodium implies that factors related to electrolyte balance and incident hypertension may be mediating factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 29 publications
1
17
0
1
Order By: Relevance
“…38 Study also showed that low serum K is associated with stroke in people with cardiovascular disease, hypertension and diabetes mellitus. 39 Our results showed that MgSO 4 therapy could prevent hypokalemia in MgSO 4 -treated groups. There was a positive association between free thyroxine levels in middle-aged and elderly subjects and atherosclerosis throughout the whole disease spectrum, which was not dependent on cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 50%
“…38 Study also showed that low serum K is associated with stroke in people with cardiovascular disease, hypertension and diabetes mellitus. 39 Our results showed that MgSO 4 therapy could prevent hypokalemia in MgSO 4 -treated groups. There was a positive association between free thyroxine levels in middle-aged and elderly subjects and atherosclerosis throughout the whole disease spectrum, which was not dependent on cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 50%
“…Besides, hyperkalemia is a threatening symptom in ESRD resulting due to reduced kidney function and conditions like the transcellular shift in insulin deficiency. The population-based reports of the Malmo preventive project cohort study showed a positive and significant association between the elevation of serum potassium per mmol/l and an increase in stroke (ischemic and hemorrhagic) risk and mortality (Johnson et al, 2017). Dysnatremia, especially hyponatremia, has significant mortality pertaining to a risk factor in stroke (Zhang et al, 2015).…”
Section: Acid-base Balancementioning
confidence: 99%
“… Drugs are involved in 80.5% of hospital-acquired hyperkalemia in older patients. Among these drug-induced hyperkalemia: (1) 79.2% are multifactorial through the combination of at least one drug with a precipitating factors; and (2)  Prevention of hospital-acquired hyperkalemia needs to take account of precipitating factors during the medication reconciliation by pharmacist. Drug dosage may be adapted or the drug may be stopped during acute illnesses in order to avoid the adverse reaction.…”
Section: What Does This Study Add To Our Knowledge?mentioning
confidence: 99%
“…Hyperkalemia is an electrolyte disorder that is frequently observed in a hospital setting, where it is associated with a 40% elevation in the death rate . In particular, polymedication and multiple comorbidities increase the risk of hyperkalemia in older patients .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation